Library material acquisition based on association rule mining. (1st January 2014) - Hossain, Md.; Rahman, Rashedur M.
Allocation of budget is important to maintain the quality of a library and is related to the materials used in a library. However, to allocate appropriate budget for an academic library we need to derive the usage of the materials. This paper offers a model for automated budget allocation that is based on the knowledge discovery using association rules. Processing the circulation data of library to extract the statistics and association utilisation of the materials for departments is a great achievement which makes the analysis easier for calculating material utilisation for the budget allocation. This paper is based on database of the North South University Library, which is one of the first fully automated private university libraries in Bangladesh. The findings and results of this work can be used to accomplish more efficient management and budget allocation of the North South University Library.